1998
DOI: 10.3171/jns.1998.88.4.0769
|View full text |Cite
|
Sign up to set email alerts
|

Acute quadriplegia with delayed onset and rapid recovery

Abstract: The authors describe a patient with severe head injury and sepsis who became acutely quadriplegic 3 days postinjury because of a critical illness polyneuropathy (CIP) and critical illness myopathy (CIM), which resolved rapidly after treatment of the underlying infection. In only 3 days the patient developed septic shock together with flaccid quadriplegia and absent deep tendon reflexes with no clinical or radiological evidence of central nervous system deterioration. Neurophysiological studies showed an acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Satisfactory tolerance of the T-piece trial was followed by extubation, regardless of MIP, MEP, VC, or MRC values. Although weaning is commonly considered successful when there is no need for reconnection to the ventilator within 48 hrs after extubation, other investigations (15) and daily experience have shown that long-term mechanically ventilated patients, especially those with CINM, frequently require reintubation and further MV for Ͼ48 hrs after a first extubation. Therefore, to analyze the contribution of respiratory weakness to delayed weaning, we focused on the duration between awakening and successful extubation defined by absence of reintubation within 15 days after extubation.…”
Section: Methodsmentioning
confidence: 98%
“…Satisfactory tolerance of the T-piece trial was followed by extubation, regardless of MIP, MEP, VC, or MRC values. Although weaning is commonly considered successful when there is no need for reconnection to the ventilator within 48 hrs after extubation, other investigations (15) and daily experience have shown that long-term mechanically ventilated patients, especially those with CINM, frequently require reintubation and further MV for Ͼ48 hrs after a first extubation. Therefore, to analyze the contribution of respiratory weakness to delayed weaning, we focused on the duration between awakening and successful extubation defined by absence of reintubation within 15 days after extubation.…”
Section: Methodsmentioning
confidence: 98%
“…The severity of peripheral muscle weakness is widely variable and can be profound in some cases, manifesting symptoms of paralysis (16). The most widely used clinical tool to assess peripheral muscle strength at the bedside is the Medical Research Council examination, which incorporates strength testing of three muscle groups in each limb with assignment of scores on a scale of 1 to 5.…”
Section: Clinical Assessment Of Skeletal Muscle Strength In Criticallmentioning
confidence: 99%
“…These intensive care 'de novo' pathologies can affect up to 80 % of patients intubated for more than two weeks [5][6][7][8][9].They also highly increase the risks for secondary complications such as pneumonia, deep vein thrombosis and pulmonary embolism. It is not clear whether these entities have a common or separate origin.Muscle biopsies from intensively treated patients revealed three morphologically distinct types of critical illness myopathy (CIM): (i) myopathy with unspecific morphological alterations [7,10], (ii) myopathy with selective loss of myosin filaments, i. e. thick-filament myopathy [11][12][13] and (iii) acute necrotizing myopathy of intensive care [14,15].…”
Section: Introductionmentioning
confidence: 97%